FACTORS OF CORONARY HEART DISEASE IN AMOUNT OF AGES > 35 YEARS IN THE TANJUNG MORAWA REGION - Rangkuty, Meisa Putri; Susanti, Nofi; Dalimunthe, Nadiyah Rahma; Br Ginting, Radha Agri (HEARTY, 2025)
Although coronary heart disease (CHD) is not contagious, its prevalence is increasing globally and in Indonesia. According to estimates, coronary heart disease will account for 36% of all deaths in 2020, making it the leading cause of death. This figure is twice as high as the death rate from cancer. The aim of this study was to identify risk factors for coronary heart disease in residents of Tanjung Morawa District aged over 35 years. To collect data for this research, 30 respondents filled out a previous questionnaire which was created using Google Form and validated. Three out of thirty respondents in Tanjung Morawa Regency, who were over 35 years old, suffered from coronary heart disease. Physical activity, smoking habits, and diet all impact the prevalence of coronary heart disease.